Disorders of gaze related to vertigo: physiological mechanisms of vestibuloocular and optokinetic reflex - Saborío Morales, Lachiner (2016)
Vestibulo-ocular and optokinetic reflex are evoked by changes in head position or movement of the visual field, the result is a nystagmus, defined by a slow phase and subsequently a rapid phase. The objective of this work is to explain the physiological mechanism involved in these reflexes. The pathways explaining the generation of these responses include a complex integration system of the motor vestibular system, ocular system, many nucleus in the brainstem, cerebellum, somatosensory cortex and motor cortex. While integration is different for each reflex, both share some estructures related with ocular movements.